FINANCIAL-ECONOMIC ANALYSIS OF FRUIT AND VEGETABLE PRODUCER GROUPS IN POLAND, AND CONDITIONS FOR THE FUNCTIONING OF PRODUCER GROUPS - Dawid Olewnicki; Ewa Sabała; Dagmara Stangierska (Polityki Europejskie, Finanse i Marketing, 2021)
Poland occupies a high position in both global and European fruit and vegetable production. The large number of small-sized farms has been one of the problems of Polish agriculture for years.National and EU financial help has increased interest in associating producers into groups. The effective functioning of these groups is conditioned by many factors related to the specificity ofhorticultural production, legislation and the market situation. Organizations on the fruit and vegetable market show significant variation in functioning as well as in the production andeconomic results achieved.The aim of the article is to assess the financial and economic situation and provide strategic analysis of the conditions for the operation of fruit and vegetable producer groups in Poland.Research was conducted on the basis of data contained in the financial statements from 2016-2017 and the financial liquidity and profitability ratios calculated on their basis. A general assessmentof the conditions needed for the functioning of producer groups is also presented in the paper.Low profitability and financial liquidity of producer groups were noted in the analyzed years. Key strategic factors for the functioning of producer groups included: the visible impact offinancial assistance, the functioning of producer groups and economies of scale resulting from greater aggregation of competition, and the fact that farmers are still reluctant to associate andoften have limited business competences to run producer groups.